2012
DOI: 10.1007/s00268-012-1489-0
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancements in Medical Simulation: Patient‐Specific Virtual Reality Simulation

Abstract: PSVR is a promising technological advance within medicine. The majority of simulators are still in the prototype phase. As further developments unfold, the validity of PSVR will have to be examined much like generic VR simulation for training purposes. Nonetheless, similar to the aviation, military, and sport industries, operative performance and patient safety may be enhanced by the application of this novel technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 33 publications
0
64
0
5
Order By: Relevance
“…16,17 In fact Haluck and colleagues 16 have shown that the use of virtual reality or CAS for the training of residents can have many advantages. Computer simulation is very well documented and has been used successfully in the military and in the aviation field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 In fact Haluck and colleagues 16 have shown that the use of virtual reality or CAS for the training of residents can have many advantages. Computer simulation is very well documented and has been used successfully in the military and in the aviation field.…”
Section: Discussionmentioning
confidence: 99%
“…Computer simulation is very well documented and has been used successfully in the military and in the aviation field. Its use and interest as an educational tool in the medical field is rapidly growing; [16][17][18][19][20] some universities even have dedicated departments for the virtual training of future medical practitioners. Accordingly, the number of orthopedic surgeons using navigation techniques is also increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patient-specific models have been designed in VR simulation to answer the "ceiling effect associated with the fixed nature of the anatomy model" described by Essani et al (35). Patient-specific models have been designed on various medical fields such as vascular, craniofacial, rectal surgery, neurosurgery, or percutaneous interventions (36). Finally, VR simulators have also been developed and validated in the field of robotic surgery (37).…”
Section: Are Vr Simulators Better Than Vt?mentioning
confidence: 99%
“…A recent state of the art on researches into patientspecific virtual reality medical simulation is presented in [16]. The primary potentials of those simulators are also training and planning rehearsal but few of them have metrics, face an content validation and none of them use ultrasound guidance and simulate respiration behavior.…”
mentioning
confidence: 99%